2005
DOI: 10.1079/ijt200586
|View full text |Cite
|
Sign up to set email alerts
|

Contribution à l'évaluation des potentialités d'Encarsia sp. (Hymenoptera: Aphelinidae) comme agent de lutte biologique contre la mouche blanche du cotonnier, Bemisia tabaci (Homoptera: Aleyrodidae) au Burkina Faso

Abstract: Encarsia sp. est le principal ennemi naturel de la mouche blanche Bemisia tabaci (Gennadius), un important ravageur du cotonnier dans l'Ouest du Burkina Faso. L'utilisation de ce parasitoïde solitaire en lutte biologique est envisagée mais ses potentialités réelles restent à déterminer. Dans cette perspective, quelques paramètres démographiques d'Encarsia sp. ont été étudiés et des lâchers sous cage ont été réalisés. Encarsia sp. peut se développer sur chacun des quatre stades larvaires de B. tabaci obtenus da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…their harmful impact on potential natural enemies (Gnankiné et al 2005), on the environment, and on the human health. This practice also leads to high levels of resistance that can appear rapidly in whiteflies because of their high fecundity and short generation time (Denholm et al 1998, Perring 2001.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…their harmful impact on potential natural enemies (Gnankiné et al 2005), on the environment, and on the human health. This practice also leads to high levels of resistance that can appear rapidly in whiteflies because of their high fecundity and short generation time (Denholm et al 1998, Perring 2001.…”
mentioning
confidence: 99%
“…As a consequence, these insecticides, which act on the insect nervous system and induce insect paralysis and death, become inefficient. Moreover, it has been shown that they have a negative impact on the populations of natural enemies of B. tabaci (Gnankiné et al 2005, Simmons et al 2011. Therefore, there is a real need to develop efficient, safer, and environmentally friendlier alternative methods that have the potential to replace chemical pesticide in terms of B. tabaci control.…”
mentioning
confidence: 99%